International encyclopedia of ergonomics and human factors - Karwowski, Waldemar, 1953- (CRC/Taylor & Francis, 2006)
Reviews applications, tools, and innovative concepts related to ergonomic research.
Keywords: Human engineering -- Encyclopedias.; Human beings.; Human engineering.; Humans; elektronické knihy; electronic books